Peningkatan Literasi Informasi Televisi Bagi Aparatur Desa Sebagai Sarana Validasi Berita Bohong (Hoaks) di Desa Smartpolitan Wantilan Kabupaten Subang - Tresia Wulandari; Kiki Nurjaman; Lisma Nadia Laehmanah; Ziqra Adhi Hamzah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Smartpolitan Village is a village development concept that integrates information and communication technology (ICT) in resource management and public services to improve the quality of life of the community. For this reason, this Community Service activity is entitled